Asia official British documents 1945-1965 on cd-rom selected documents from the End of World War II to Vietnam - Kandiah, Michael David (London: Routledge, 1999)
This vast collection of government records forms a major archive of official documents relating to matters in the Asia Pacific region, previously available only at Public Record Office in London.
CD is not accessible or may be corrupted - 20 Oct 2009
System requirements: 90 MHZ Pentium processor; 8MB of RAM available hard disk space; quad speed CD-ROM drive; Windows 3.11 or higher
Keywords: Great Britain -- Foreign relations -- Asia, Southeastern -- Sources; Asia, Southeastern -- History -- 1945- -- Sources; Asia, Southeastern -- Foreign relations -- Great Britain -- Sources